Utilization of Cigarette Box Waste to Become a Mangrove Batik Printer in Tanjung Rejo Village, Percut Sei Tuan District - Tri Rahayu; Wiwin Nurzanah; Fahrizal Zulkarnain; Sri Asfiati; Yunita Pane (Universitas Lancang Kuning, 2023)
There are not many uses of mangroves as natural batik dyes, due to the lack of information available about these natural ingredients. The process of using natural colors in batik techniques has been carried out by our ancestors for generations until synthetic colors were found which were considered practical and economical. Batik is a commodity that is currently growing rapidly. Batik has now become a fashion trend in all walks of life, making batik craftsmen more enthusiastic about developing their products. In this process, batik is still stamped manually. This village has batik activities using natural dyes, namely mangrove stems around Tanjung Rejo Village. The proposing team is interested in PKK activities in Tanjung Rejo Village and intends to make them Partners. The partners of the Proposal Team are a group of Batik Mangrove Lestari craftsmen chaired by Mrs. Hamidah under the Tanjung Rejo Village PKK coordinator. This group is able to produce one batik cloth per person per week and one person printed batik 10 cloths/week, which can be sold for 300,000 to 1,000,000 per batik. But right now they are struggling with the rising prices of batik materials, they are confused about how much more batik is for sale, especially batik printers, the increase is up to 100% for a price of around 1,000,000 / pcs with 1 type of motif. While the people of Tanjung Rejo Village themselves still make batik manually using a canting and a printer. Since it was the one they used to use, with the price of the printer going up to 100% they were at a loss as to how to outsmart it. Meanwhile, with 1 batik, 1 motif and it is impossible for them to change the motif continuously while the price reaches 1,200,000/pcs for the printer. For this reason, the proposing team tried to devise creative ideas to use cigarette boxes to become batik printers later, considering that many cigarette box wastes are scattered around Tanjung Rejo Village. Because the creativity that will be made is one that can increase their income in Tanjung Rejo Village besides selling batik, they can also sell batik printers from cigarette box waste later outside of Tanjung Rejo Village. From the survey results, several problems were found in Tanjung Rejo Village: the lack of knowledge of using cigarette boxes to make mangrove batik printers, not knowing how to make good and strong batik printing designs, and not knowing about marketing and management techniques. For this reason, the proposing team tried to solve the partner's problem, namely by providing training on the use of cigarette boxes as mangrove batik printers, training on making batik printing motif designs, and training on marketing and management techniques